MENINGKATKAN KEMAMPUAN PENGURANGAN MELALUI PENDEKATAN BERMAIN DENGAN MENGGUNAKAN BENDA KONKRIT BAGI ANAK TUNAGRAHITA RINGAN - Yurmailis Yosfan Azwandi Rahmatrisilvia (Universitas Negeri Padang, 2013)
This study originated from an observation which is done at slb lubuk kilangan, padang. the writer found a child who is having problems, mild mental retardation in math in particular on the reduction. This research aims for a reduction in the ability of children can be improved through the use of media approaches playing with concrete objects. This research use experimental approach in the form of single subject research (SSR) with a research design using a-b design. This research‘s subject is a child's mild mental retardation. The target behavior is to increase the ability of reduction by answering 10 questions on the reduction on student worksheets. Procedures of data collection are through direct observations of the results of the exercise are given to children in improving the ability of reduction. Data were taken through giving questions procedure which gives the value of the number of questions answered correctly on the student’s worksheet. Technique data analysis based on observational data in the form of a visual analysis of the graph. The results of this study indicate that the approach through playing with concrete objects can improve the reduction of ATR. this is proven by the analysis which is the disposed direction increased